2016
DOI: 10.1177/0047287515627028
|View full text |Cite
|
Sign up to set email alerts
|

Does Political and Economic Freedom Matter for Inbound Tourism? A Cross-National Panel Data Estimation

Abstract: The paper examines the impact of political and economic freedom on inbound tourism for over 110 countries during 1995-2012. Panel country fixed-effects techniques are utilized to examine the relationship after controlling for other factors that contribute to inbound tourism.The results show that civil liberties and economic freedom (among several other freedom measures) are positively and significantly associated with inbound tourism. Examination of the moderation effect reveals that civil liberties (economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 33 publications
(54 reference statements)
6
97
0
2
Order By: Relevance
“…Gozgor et al (2017) find that the greater role of the military in politics is negatively related to the inbound tourism in Turkey for the period from 1984 to 2014. Finally, using the fixed-effects estimations, Saha et al (2017) observe that there are the positive effects of the civil liberties and the economic freedom on the inbound tourism in the panel dataset of 110 countries for the period from 1995 to 2012.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Gozgor et al (2017) find that the greater role of the military in politics is negatively related to the inbound tourism in Turkey for the period from 1984 to 2014. Finally, using the fixed-effects estimations, Saha et al (2017) observe that there are the positive effects of the civil liberties and the economic freedom on the inbound tourism in the panel dataset of 110 countries for the period from 1995 to 2012.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Many studies in the literature analyze macroeconomic and non-economic determinants of inbound tourism. For instance, conflicts, political instability, security, and terrorism are also used as potential uncertainty sources affecting tourism development (Ghaderi et al, 2017;Saha and Yap 2014;Saha et al, 2017). The negative impact of terrorism on inbound tourism is also a well-known fact (Araña and León, 2008;Enders et al, 1992;Thompson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The study was based on a sample of 85 countries and showed that countries that are interested in improving the business climate, such as promoting economic freedom, are the beneficiaries rather than the multinational companies. As for Saha et al (2017) found a causal link between economic freedom and political inbound tourism for more than 110 countries during 1995-2012. In general, most studies confirm the importance and role of economic freedom in attracting foreign direct investment and raising the rate of economic growth.…”
Section: Literature Reviewmentioning
confidence: 96%
“…However, the other most influential paper treating the link of interest has employed different methodology, thus the direct comparison was not possible. Apart from this it is important to emphasize that Saha et al (2016) report a positive link of economic freedom on tourism industry.…”
Section: Resultsmentioning
confidence: 99%